2021
DOI: 10.1111/1475-6773.13860
|View full text |Cite
|
Sign up to set email alerts
|

Health information technology to improve care for people with multiple chronic conditions

Abstract: Objective To review evidence regarding the use of Health Information Technology (health IT) interventions aimed at improving care for people living with multiple chronic conditions (PLWMCC) in order to identify critical knowledge gaps. Data Sources We searched MEDLINE, CINAHL, PsycINFO, EMBASE, Compendex, and IEEE Xplore databases for studies published in English between 2010 and 2020. Study Design We identified studies of health IT interventions for PLWMCC across three domains as follows: self‐management supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 127 publications
1
32
0
2
Order By: Relevance
“…A recent literature review suggested that a lack of attention has been given to understanding attitudes towards the sharing of health and lifestyle data with third parties, which suggests the need for future study. 70 …”
Section: Discussionmentioning
confidence: 99%
“…A recent literature review suggested that a lack of attention has been given to understanding attitudes towards the sharing of health and lifestyle data with third parties, which suggests the need for future study. 70 …”
Section: Discussionmentioning
confidence: 99%
“…Learning health systems are data-driven, healthcare delivery processes of continuous quality improvement, providing patients with higher quality, safer, and more effective care by utilizing informatics and data science to translate research into evidence-based practice. 31,32 However, opportunities to improve multimorbidity patient outcomes are widely constrained by the current informatics infrastructure that is used to characterize the outcomes of patients with multimorbidity. 2,4,6,[31][32][33][34][35] To date, these informatics constraints have included the subjectivity (i.e., recall bias) of analyzing self-reported data gathered through national databases (i.e., National Health Interview Survey) and the focus on specific sets of chronic conditions versus all combinations that could potentially encompass multimorbidity (i.e., Behavioral Risk Factor Surveillance System Surveys).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, adding psychosocial variables for patients with higher multimorbidity appeared to be a more consistently powerful predictor of utilization than attempting to use individual conditions; this lends itself to use in more comprehensive models of care management and coordination. 44,45 Previous work has looked at the benefits of collecting SDOH as psychosocial factors. A review showed increasing rates of a structured collection of social determinants in EHRs showed promise in use in prediction and quality improvement, but many barriers exist, including a lack of agreement on how, when, and why to collect the data.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, patients with diabetes had better prediction models for hospitalizations from housing insecurity and financial insecurity, but not for depression and social isolation. Thus, adding psychosocial variables for patients with higher multimorbidity appeared to be a more consistently powerful predictor of utilization than attempting to use individual conditions; this lends itself to use in more comprehensive models of care management and coordination 44,45…”
Section: Discussionmentioning
confidence: 99%